Tradisi Nunas Kecap Mandi Di Pura Dalem Gede Desa Pakraman Galiran Di Kabupaten Bangli (Perspektif Pendidikan Agama Hindu) - Pande Saputra, I Kadek; Sudarsana, I Ketut; Wijaya Mahardika, I.G.N. Agung (Jurnal Penelitian Agama Hindu, 2019)
These problems have been examined by using several theories, namely religious theory, struktural functionalism theory, and values theory. The method was unsed in thus research was qualitativ method which the process consists of detemining the resear location, detarmining the types and the data sources,determining the research instruments, determining the data collection method by using observation, interview, dokumen study, data analysis and presentation of the resul of data analysis. 1) The procesion of nunas Kecap Mandi tradition at Dalem Gede temple in Pakraman Galiran village could be described in three tages of implementation, the first stage, the core stage, and the final stage. The frist stage in carried out the process in making Kecap Mandi. At the core stage is carried out of nunas Kecap Mandi procesion which this process had been begun with Nedunang Ida Bhatara tedun to pelinggih Dasar, praying, nunas Kecap Mandi an nunas Wangsupada (Tirta). Then at the final stage is ceriied out the process of ngewaliang Ida Bhatara to Pelinggih Pengaruman. 2) The function of nunas Kecap Mandi tradition at Dalem Gede temple in Pakraman Galiran village are pleading prosperity function, social function and education functiona. 3) The Hindu education values contained of nunas Kecap Mandi tradition at Dalem Gede temple in Pakraman Galiran village are the tattwa velues, moral velues, and ceremony values.